2009
DOI: 10.1038/nm.2070
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human neutrophil alloantigen-3a

Abstract: Transfusion-related acute lung injury (TRALI) is a frequent cause of transfusion-associated morbidity and mortality. Severe TRALI is often due to antibodies in blood components directed against the human neutrophil alloantigen-3a (HNA-3a). We show here that the HNA-3a antigen arises from a nucleotide polymorphism in the choline transporter-like protein-2 gene (SLC44A2), with the resulting variation at amino acid position 154 determining the reactivity of the protein with HNA-3a-specific antibodies; the variant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
149
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(164 citation statements)
references
References 19 publications
10
149
2
3
Order By: Relevance
“…Third, the approach we developed for the identification of the allospecificity was reported by others during the time of our study (42)(43)(44). Our results are one more example that shows the power of detection, no matter whether it is an alloimmune or an auto- immune disease, for the discovery of Ab specificities.…”
Section: Discussionsupporting
confidence: 53%
“…Third, the approach we developed for the identification of the allospecificity was reported by others during the time of our study (42)(43)(44). Our results are one more example that shows the power of detection, no matter whether it is an alloimmune or an auto- immune disease, for the discovery of Ab specificities.…”
Section: Discussionsupporting
confidence: 53%
“…It has been demonstrated previously that direct exposure of resting neutrophils to anti-HNA-3a alone is not sufficient to induce ROS. 12,13 However, ROS was detectable in anti-HNA-3a IgG-primed neutrophils followed by formyl-methionyl-leucyl phenylalanine stimulation. 13 In contrast to this report, we did not observe a significantly augmented respiratory burst reaction neither in resting nor in formyl-methionyl-leucyl phenylalanine-treated neutrophils primed with anti-HNA-3a antibodies using 2 different methods (2′,7′-dichlorofluorescin diacetate and ferricytochromec).…”
Section: Discussionmentioning
confidence: 98%
“…34,42 It is well known that anti-HNA-3a antibodies form strong neutrophil agglutinates in some in vitro assays, such as the GAT assay. Recently, Greinacher et al 12 demonstrated that this mechanism is FcγR independent. The question whether this phenomenon occurs in vivo and participates in the mechanism of TRALI is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally thought, although unproven, that either receptor cross-linking or direct activation of the receptor may lead to signaling events that cause neutrophil activation and, subsequent, deterioration of the lung vascular integrity. 10,13,32,33 This mechanism is not likely in the case of HLA class II antibodies, because HLA class II antigens are normally not present on neutrophils (see below). Here, we observed, however, that HLA class II antibodies can bind to monocytes that express the cognate antigen and thereby induces the release of potent cytokines and LTB 4 .…”
Section: Discussionmentioning
confidence: 99%